DEVELOPING A NEW HYBRID PEDAGOGY: A CASE STUDY OF PROJECT-BASED LEARNING INTEGRATING COMMUNITY ENGAGEMENT AND DIGITAL COLLABORATION - Sofia Pereira; Carlos Lopes; Marta Carvalho (Yayasan Adra Karima Hubbi, 2025)
The rapid evolution of hybrid learning environments has encouraged educators to explore pedagogical models that bridge academic theory, community engagement, and digital collaboration. Conventional hybrid learning, while flexible, often lacks experiential relevance and authentic social application. This study seeks to develop and evaluate a new hybrid pedagogy that integrates Project-Based Learning (PBL) with community engagement and digital collaboration to foster deeper learning, civic responsibility, and digital literacy among university students. The research aims to identify how this integrated model enhances student motivation, critical thinking, and collaborative problem-solving within real-world contexts. A qualitative case study design was employed involving 42 undergraduate students enrolled in an education program at a public university. The implementation spanned one academic semester, during which students collaborated with local community partners through hybrid PBL projects supported by digital platforms such as Padlet, Google Workspace, and Zoom. Data were collected through reflective journals, interviews, project assessments, and observation notes, then analyzed thematically to uncover learning patterns and pedagogical impacts. The findings reveal that the hybrid PBL model significantly improved students’ engagement, teamwork, and contextual understanding, while strengthening their ability to integrate digital tools for collaborative inquiry. Participants reported increased confidence in applying theoretical knowledge to community-based challenges. The study concludes that the integration of community engagement and digital collaboration within PBL provides a sustainable hybrid pedagogy for higher education. This model promotes authentic, transformative, and socially responsible learning experiences that align with 21st-century educational goals.